Coordinated Regulation of TIP60 and Poly(ADP-Ribose) Polymerase 1 in Damaged-Chromatin Dynamics - Ikura, Masae (Mol Cell Biol, 2016)
The dynamic exchange of histones alleviates the nucleosome barrier and simultaneously facilitates various aspects of cellular DNA metabolism, such as DNA repair and transcription. In response to DNA damage, the acetylation of Lys5 in the histone variant H2AX, catalyzed by TIP60, plays a key role in promoting histone exchange; however, the detailed molecular mechanism still is unclear. Here, we show that the TIP60 complex includes poly(ADP-ribose) polymerase 1 (PARP-1). PARP-1 is required for the rapid exchange of H2AX on chromatin at DNA damage sites. It is known that PARP-1 binds dynamically to damaged chromatin and is crucial for the subsequent recruitment of other repair factors, and its auto-poly(ADP-ribosyl)ation is required for the dynamics. We also show that the acetylation of histone H2AX at Lys5 by TIP60, but not the phosphorylation of H2AX, is required for the ADP-ribosylation activity of PARP-1 and its dynamic binding to damaged chromatin. Our results indicate the reciprocal regulation of K5 acetylation of H2AX and PARP-1, which could modulate the chromatin structure to facilitate DNA metabolism at damage sites. This could explain the rather undefined roles of PARP-1 in various DNA damage responses.